Sistem Pendukung Keputusan Penilaian Kinerja Karyawan Menerapkan Metode TOPSIS - Ahmad Rifqi; Rima Tamara Aldisa (STMIK Budi Darma, 2023)
The development of information technology has the potential to affect the operational level and complexity of human tasks. The success of an organization or company in achieving its set goals is highly dependent on the readiness of its human resources. The role of employees in a company or agency is very vital, because those who meet the needs of organizational skills can increase overall productivity. Therefore, a computer system is needed to meet these information needs, namely a decision support system (DSS). In this study, researchers conducted research on employee performance using the TOPSIS method and used several existing criteria, namely responsibility, discipline, neatness, cooperation and honesty which are expected to help in determining good employee research and can be applied in institutions or companies. Based on the research that has been done, the highest result is obtained by the value of 0.672 On behalf of Erina as the employee with the highest score